Training, environmental and nutritional practices in indoor cycling: an explorative cross-sectional questionnaire analysis - Peeters, W. M.; Coussens, A. H.; Spears, I.; Jeffries, O. (Frontiers in Sports and Active Living, 2024)
Indoor cycling at home has grown rapidly in recent years facilitated by advances in technology and gamification. However, there is limited data on individual's training practices when cycling indoors. Using a single-time point, cross-sectional questionnaire, we gathered information on equipment, environmental considerations, training practices and nutrition during indoor cycling. Following 492 responses, external variables (weather; 88.4%, lack of daylight; 56.3%), time efficiency (81.9%) and general fitness (70.9%) were most frequently cited as reasons to engage in indoor cycling. "Smart" turbo trainers linked to a mixed-reality cycling software were most frequently reported in equipment set -up. 78% of participants attempted to control temperature with 96% of these participants using at least 1 fan to control airflow. The volume of indoor training differed between seasons (winter: 6h10 ± 3 h 30, summer 2h52 ± 2h57, p < 0.001), and structured (61.9%) and unstructured work-outs (64.7%) were completed more than once a week with fewer participants engaging in competitive/racing events (20.9%). 98% percent of participants consumed fluids with an average fluid intake of 0.74 ± 0.28 L/h. Dependent on type of work-out, participants reported less planning of carbohydrate and protein intake during short-duration work-outs ( 40-60%) relative to longer-duration work-outs ( 56-80%). Caffeine use was the most frequently reported ergogenic aid. Together we report indoor cycling practices with respect to training equipment, considerations of environmental and nutritional strategies and training habits. Our findings could be used to support the development of future research and indoor training guidelines.